2018
DOI: 10.1101/342352
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Widespread selection and gene flow shape the genomic landscape during a radiation of monkeyflowers

Abstract: Speciation genomic studies aim to interpret patterns of genome-wide variation in light of the processes that give rise to new species. However, interpreting the genomic ‘landscape’ of speciation is difficult, because many evolutionary processes can impact levels of variation. Facilitated by the first chromosome-level assembly for the group, we use whole-genome sequencing and simulations to shed light on the processes that have shaped the genomic landscape during a recent radiation of monkeyflowers. After infer… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
88
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(95 citation statements)
references
References 102 publications
6
88
1
Order By: Relevance
“…Our modelling approach indicated that approximately 45-50% of the genome was undergoing linked selection (Table 2) and that effective population size (ܰ ) was locally reduced to approximately 10-20% of its size due to Hill-Robertson interference ( Table 2). The role of such a linked selection process, unrelated to speciation, is increasingly recognized as being implicated in observed patterns of genome-wide divergence (Cruickshank & Hahn 2014, Burri 2017, and has been empirically demonstrated elsewhere (e.g., Burri et al 2015, Roux et al 2016, Wang et al 2016, Rougemont & Bernatchez, 2018, Stankowski et al 2019. Admittedly, further estimates of recombination rate variation along the genome will be needed to help disentangling how linked selective processes are currently affecting genome-wide divergence patterns.…”
Section: An Ongoing Speciation Process Among Lineagesmentioning
confidence: 99%
“…Our modelling approach indicated that approximately 45-50% of the genome was undergoing linked selection (Table 2) and that effective population size (ܰ ) was locally reduced to approximately 10-20% of its size due to Hill-Robertson interference ( Table 2). The role of such a linked selection process, unrelated to speciation, is increasingly recognized as being implicated in observed patterns of genome-wide divergence (Cruickshank & Hahn 2014, Burri 2017, and has been empirically demonstrated elsewhere (e.g., Burri et al 2015, Roux et al 2016, Wang et al 2016, Rougemont & Bernatchez, 2018, Stankowski et al 2019. Admittedly, further estimates of recombination rate variation along the genome will be needed to help disentangling how linked selective processes are currently affecting genome-wide divergence patterns.…”
Section: An Ongoing Speciation Process Among Lineagesmentioning
confidence: 99%
“…Schilling et al, 2018) and empirically (e.g. Chapman et al, 2016;Safran et al, 2016;Doellman et al, 2018;Stankowski et al, 2019). Senecio contains multiple systems where these evolutionary dynamics can be studied.…”
Section: Population Genomics Of Ecological Speciationmentioning
confidence: 99%
“…Furthermore, studying variation in levels of differentiation within and between closely related species has the potential to yield important insights into the process of speciation (Ravinet et al, 2017; Wolf & Ellegren, 2017). Studies in a broad range of taxonomic groups have revealed a picture of a highly heterogeneous genomic landscape with peaks and valleys of diversity and differentiation (Han et al, 2017; Nadeau et al, 2012; Stankowski et al, 2019; Turner, Hahn, & Nuzhdin, 2005). Local peaks of elevated divergence are usually referred to as “speciation islands” and are thought to represent regions that drive the reproductive isolation between incipient species (Abbott et al, 2013; Wu, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…As deleterious mutations are assumed to be much more common compared to beneficial mutations, background selection has been argued to play a major role in the evolution of diversity (Burri, 2017; Lohmueller et al, 2011; Phung et al, 2016). However, many recent simulation studies have shown that background selection alone is far from sufficient for generating the heterogenous genomic landscapes observed in empirical studies of recently diverged species, and other evolutionary processes (such as positive selection) are thus required to explain the observed patterns (Matthey‐Doret & Whitlock, 2019; Stankowski et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation